High performance embedded computing : architectures, applications, and methodologies - Wolf, Marilyn, 1958- (Morgan Kaufmann, 2014)
High-Performance Embedded Computing, Second Edition, combines leading-edge research with practical guidance in a variety of embedded computing topics, including real-time systems, computer architecture, and low-power design. Author Marilyn Wolf presents a comprehensive survey of the state of the art, and guides you to achieve high levels of performance from the embedded systems that bring these technologies together. The book covers CPU design, operating systems, multiprocessor programs and architectures, and much more. Embedded computing is a key component of cyber-physical systems, which combine physical devices with computational resources for control and communication. This revised edition adds new content and examples of cyber-physical systems throughout the book, including design methodologies, scheduling, and wide-area CPS to illustrate the possibilities of these new systems. Revised and updated with coverage of recently developed consumer electronics architectures and models of computingIncludes new VLIW processors such as the TI Da Vinci, and CPU simulation Learn model-based verification and middleware for embedded systems Supplemental material includes lecture slides, labs, and additional resources.